Educational Management Courses: Leveraging Problem-Based Learning to Improve Students’ Motivation to Learn - Hasnadi, Hasnadi (Development: Studies in Educational Management and Leadership, 2025)
The purpose of this study is to measure the improvement in learner motivation prior to and subsequent to the implementation of the problem-based learning model. This quantitative study used a single-group pretest–posttest design with a sample of 42 students in the Educational Management course. Data collection was conducted in the odd semester of the 2023/2024 academic year using a motivation questionnaire developed based on Keller's theory (1987). The data were analyzed quantitatively. The results show a significant difference in learning motivation before and after the implementation of PBL. The average increase in motivation was 9.51, with an average N-gain score of 0.23, which is classified as low. These findings indicate that PBL can increase student learning motivation in the Education Management course, even though the level of increase is still in the low category. In conclusion, the application of PBL is effective in encouraging increased motivation, but accompanying strategies—such as strengthening feedback, task differentiation, or technological support—are needed to optimize its impact.